Structural insights into cholesterol sensing by the LYCHOS-mTORC1 pathway - Yu, Shang; Ding, Jin-hui; Wang, Jia-le; Wang, Weize; Zuo, Peng; Yang, Ao; Dai, Zonglin; Yin, Yuxin; Sun, Jin-peng; Liang, Ling (Nature communications, 2025)
The lysosomal cholesterol sensor LYCHOS regulates mTORC1 signaling by coupling cholesterol sensing to GATOR1-Rag GTPase modulation, yet its structural mechanisms remain unclear. Here we report six cryo-electron microscopy structures of human LYCHOS, depicting five distinct states. These are categorized into a contracted state when complexed with a sufficient amount of the cholesterol analogue cholesteryl hemisuccinate (CHS), and an expanded state when CHS is deficient. The structure forms a homodimer, within each monomer the transmembrane region is divided into a permease-like domain (PLD) and a GPCR-like domain (GLD) with two clearly defined adjacent cholesterol binding sites between them. Cholesterol binding induces a translation of GLD towards PLD and exposes the cytosolic extension of transmembrane 15, which interacts with GATOR1. Our results elucidate the structural mechanism of cholesterol sensing by the mTORC1 pathway, providing a structural basis for developing inhibitors that selectively target mTORC1 pathway by blocking LYCHOS in its expanded state. Cholesterol sensing by LYCHOS regulates mTORC1 signaling through GATOR1-Rag GTPase. Here, authors reveal cryo-EM structures of LYCHOS in various states, showing cholesterol binding shifts it from an expanded to a contracted state, exposing a cytosolic element that engages GATOR1.